2014
DOI: 10.5120/16203-5488
|View full text |Cite
|
Sign up to set email alerts
|

A Speech Encryption based on Chaotic Maps

Abstract: In this paper a new speech encryption system is presented. It is based on permutation and substitution of speech samples using secret keys in time and transform domains. The system is with multilevel to increase the security and to present an encrypted signal with low residual intelligibility. The logistic map is employed in keys generation to generate permutation and mask keys to be used in the permutation and substitution process. In order to maximize the benefits of the permutation process for the system, A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 7 publications
(4 reference statements)
0
5
0
Order By: Relevance
“…Chaos-based algorithms [19]- [23] uses chaotic maps such as logistic maps, Lorenz maps, Baker maps, and Chen maps to generate random numbers to be suitable for cryptographic needs. Some of the one and two-dimensional chaotic cryptosystems found in [14], [15], [23] are promising generators for their suitability for cryptographic applications.…”
Section: Literature Surveymentioning
confidence: 99%
“…Chaos-based algorithms [19]- [23] uses chaotic maps such as logistic maps, Lorenz maps, Baker maps, and Chen maps to generate random numbers to be suitable for cryptographic needs. Some of the one and two-dimensional chaotic cryptosystems found in [14], [15], [23] are promising generators for their suitability for cryptographic applications.…”
Section: Literature Surveymentioning
confidence: 99%
“…The size of the key space generated from this audio encryption algorithm is It can be concluded that this algorithm is robust in resisting brute force attacks compared to other algorithms (Table 4) because it has the largest key space size. Chaotic Maps Key Space Multi-scrolling -SHA 256-bit [8] 2D cosine number transform [9] 2D tent map and two Chebyshev polynomials [10] Continuation of Table 4 Circle map and modified rotation equation [11] Logistic map [12] Single NCQM [13] Double NCQM [13] 3D Lorenz -Logistic map [14] Double scrolling -SHA 256-bit (proposed)…”
Section: Key Space and Sensitivity Analysismentioning
confidence: 99%
“…Algorithm with another scheme uses a 2D tent map and two Chebyshev polynomials, which form a key space of [10]. Another article offers a circle map scheme and a modified rotation equation that produces a key space of [11], and there is an audio encryption algorithm using a logistic map with a key space of up to [12], a normalized complex quadratic map (NCQM), which produces a key space of (single NCQM) and (double NCQM) [13], and a 3D Lorenz-Logistic map with a key space formed reaching [14]. Moreover, Abdul Kadhim et al [15] proposed audio steganography with 4D grid multiwing hyper-chaotic system and introduced a speech encryption algorithm based on the Lorenz chaotic map [16]; a new speech encryption algorithm based on a dual shuffling Hénon chaotic map [17] uses a chaotic elliptic map [18].…”
Section: Introductionmentioning
confidence: 99%
“…Analog audio cipher has four main types, they are: Since 2014 researchers tried to present different algorithms for encryption analog audio data. In 2014, Saad Najim et al [31] presented multilevel speech encryption algorithm based totally on confusion and diffusion properties. They used three keys (key1, key2 and mask key) for permutation and substitution operations.…”
Section: Analog Audio Encryption Algorithmsmentioning
confidence: 99%